Saint Vincent and the Grenadines : OECS Fiscal Issues, Policies to Achieve Fiscal Sustainability and Improve Efficiency and Equity of Public Expenditures - World Bank (Washington, DC, 2012)
The central theme of the St. Vincent and the Grenadines Fiscal Issues report, the first Public Expenditure Review conducted by the World Bank in this country, is that in order to restore rapid economic growth, ensure medium-term fiscal sustainability under the umbrella of the Eastern Caribbean Currency Union (ECCU) and protect the social achievements realized in the past decades, the country will best benefit from: (a) tightening fiscal policy, mostly through expenditure cuts; (b) an increase in the efficiency of public investments and public service delivery; (c) strengthening regulation and efficiency of public utilities and sea/air transport; and (d) promoting education and skills development to prepare the population, notably the poor, to take advantage of new opportunities in the global environment.